2009
DOI: 10.1158/1055-9965.epi-09-0287
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes among Adult Survivors of Childhood Cancer in the British Childhood Cancer Survivor Study

Abstract: Purpose: We used data from the first large-scale overwhelmingly population-based study (a) to quantify the risk of adverse pregnancy outcomes in survivors of childhood cancer in relation to cancer type and treatment and (b) to assess live birth rates relative to the general population. Methods: A questionnaire, including questions inquiring about pregnancy outcomes, was completed by 10,483 survivors. A total of 7,300 pregnancies were reported. Odds ratios (OR) for live birth, miscarriage, termination, stillbir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
129
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 37 publications
8
129
2
2
Order By: Relevance
“…8 The British Childhood Cancer Survivor Study reported only 31% of survivors having at least one child which is approximately two-thirds of what would be expected from British population statistics. 9 Just 3% of Dutch male and 15% of Dutch female survivors reported biological children. 10 Reports from the Childhood Cancer Survivor Study show 15% of men and 27% of women survivors with children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 The British Childhood Cancer Survivor Study reported only 31% of survivors having at least one child which is approximately two-thirds of what would be expected from British population statistics. 9 Just 3% of Dutch male and 15% of Dutch female survivors reported biological children. 10 Reports from the Childhood Cancer Survivor Study show 15% of men and 27% of women survivors with children.…”
mentioning
confidence: 99%
“…However, prematurity and low-birth weights have been associated with abdominal radiation. [9][10][11][12] Pivetta et al use marriage and offspring as surrogate markers for the life-long impact of cancer therapy on the social and behavioral choices of adult survivors of childhood cancer. This raises important questions regarding measurement of QOL in this population.…”
mentioning
confidence: 99%
“…Youth is certainly a protective factor, but long-term follow-up of childhood cancer patients demonstrates clear effects on ovarian reserve and reproductive potential later in life [25][26][27][28][29][30][31] . Fortunately, chemotherapeutic agents do not appear to have long-term effects on the genetic competency of surviving oocytes or on the future pregnancies themselves 32 , but based on murine data, the risk of fetal malformation might be elevated for up to 6-12 months after exposure 33 .…”
Section: Chemotherapymentioning
confidence: 99%
“…Pelvic irradiation impairs fertility and is associated with poor pregnancy outcomes, including early and midtrimester loss, preterm birth, and low birthweight 41 . The pathophysiology appears to involve vascular, endometrial, and myometrial damage 31,42 . Exposure before completion of puberty impairs normal uterine development, with a resulting reduced adult uterine volume that is refractory to estrogen replacement therapy.…”
Section: Radiation Therapymentioning
confidence: 99%
“…3 Previous studies have identified treatment-related risks, reporting an increased risk of preterm birth following ≥ 5 Gray (Gy) of uterine radiation, 3 stillbirth following ≥ 10 Gy of uterine and ovarian radiation, 4 and miscarriage following abdominal radiation. 5, 6 However, the influence of potentially modifiable prepregnancy lifestyle factors such as body mass index (BMI), smoking, heavy alcohol consumption, physical inactivity, and psychological distress on adverse pregnancy outcomes in childhood cancer survivors has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%